The structural insight of class III of polyhydroxyalkanoate synthase from Bacillus sp. PSA10 as revealed by in silico analysis - Listia Pradani; Muhammad Saifur Rohman; Sebastian Margino (Indonesian Journal of Biotechnology, 2020)
PhaC synthase is an enzyme responsible for PHA polymerization. In this work, the catalytic mechanism class III of PhaC synthase from Bacillus sp. PSA10 (BacPhaCSynt) was reported through in silico modelling approach based on the primary sequence of the PhaC synthase. The open reading frame BacPhaCSynt has been successfully isolated, cloned and overexpressed the recombinant protein in Escherichia coli BL21(DE3). To know the global architecture and catalytic mechanism, the structural prediction of BacPhaCSynt has been carried out by using MODELLER. The recombinant BacPhaCSynt exhibited monomeric molecular weight (MW) of 43.6 kDa, when it was analyzed on 12% SDS‐PAGE gel. Based on the structural prediction, BacPhaCSynt exhibited global architecture of α/β hydrolase fold, with the root mean square deviation (r.m.s.d) value of 0.94Å. The catalytic residues composition of BacPhaCSynt consists of C151, D307, and H336, but the H336 and D307 residues of the model have been distorted 62.8o and 175.2o from the corresponding residues of the template. Since the D307 is quite a distance from the H336, it might act as a general base for the activation of ‐OH group of the substrate. The results strongly suggested that the mode of action of BacPhaCSynt obeyed the covalent catalysis mechanism.